A Critique on the Book The Political Thought of Khonji, The Wandering Faqih - Mohammad Shojaeian (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The crisis that arose as a result of the decline of the Abbasid caliphate in the middle of the seventh century AH for Sunni political thought continued for centuries. This crisis in the tenth century for a prominent thinker named Roozbehan Khonji, a prominent Sunni theorist, led to the attempt to revive the caliphate by appealing to the kings who held political power in his time, rather than concerning religion. The book The Political Thought of Khonji, The Wandering Faqih examines the views and ideas of Khonji as one of the last representatives of Sunni thought in Iranian society. The present article is both a critical reading of the views of "Sheikh Khonj" and a critical review of the book. This study is organized in four parts. Criticism of the author's approach to the Safavieh rule, critical study of Khonji's opposition to Shiite political rule and anti-Iranian elements of his views are among the points that are emphasized in the present study. Also, the theory of domination, which is presented as political realism and the reduction of the epistemological position of political thought is one of the challenges that will be sought.